Randomised clinical trial: A phase 2 double‐blind study of namodenoson in non‐alcoholic fatty liver disease and steatohepatitis. Issue 11 (20th October 2021) - Safadi, Rifaat; Braun, Marius; Francis, Adi; Milgrom, Yael; Massarwa, Muhammad; Hakimian, David; Hazou, Wadi; Issachar, Assaf; Harpaz, Zivit; Farbstein, Motti; Itzhak, Inbal; Lev‐Cohain, Naama; et al.
Summary: Background: Namodenoson, an A3 adenosine receptor (A3AR) agonist, improved liver function/pathology in non‐alcoholic steatohepatitis (NASH) preclinical models. Aim: To evaluate the efficacy and safety of namodenoson for the treatment of non‐alcoholic fatty liver disease (NAFLD) with or without NASH Methods: This phase 2 study included 60 patients with NAFLD (ALT ≥60 IU/L) who were randomised (1:1:1) to oral namodenoson 12.5 mg b.d. (n = 21), 25 mg b.d. (n = 19), or placebo (n = 20) for 12 weeks (total follow‐up: 16 weeks). The main efficacy endpoint involved serum ALT after 12 weeks of treatment. Results: Serum ALT decreased over time with namodenoson in a dose‐dependent manner. The difference between change from baseline (CFB) for ALT in the namodenoson 25 mg b.d. arm vs placebo trended towards significance at 12 weeks ( P  = 0.066). Serum AST levels also decreased with namodenoson in a dose‐dependent manner; at 12 weeks, the CFB for 25 mg b.d. vs placebo was significant ( P  = 0.03). At Week 12, 31.6% in the namodenoson 25 mg b.d. arm and 20.0% in the placebo arm achieved ALT normalisation ( P  = 0.405). At week 16, the respective rates were 36.8% and 10.0% ( P  = 0.038). A3AR expression levels were stable over time across study arms. Both doses of namodenoson were well tolerated with no drug‐emergent severe adverse events, drug‐drug interactions, hepatotoxicity, or deaths. Three adverse events were considered possibly related to study treatment: myalgia (12.5 mg b.d. arm), muscular weakness (25 mg b.d. arm), and headache (25 mg b.d. arm). Conclusion: A3AR is a valid target; namodenoson 25 mg b.d. was safe and demonstrated efficacy signals (ClinicalTrials.gov #NCT02927314). Abstract : Randomised clinical trial: A phase 2 double‐blind study of namodenoson in non‐alcoholic fatty liver disease and steatohepatitis. https://doi.org/10.1111/apt.16664